Academic Senate Minutes 2006-09-14 - Academic Senate:::::::::
Chair Report. Approval and amendment of agenda. Approval of minutes of 8/31/06. Approval of John Kunat to Student Union Board. End of Year reports for Academic Advising and FSAC. Update on WASC. President Report. Animal Care policy first reading. Resolved that as the Senate expresses great concern regarding the adverse fiscal impact on this campus, we recommend the revenue bond project be rejected. Approved. Good of the Order.